Association between community average body mass index and perception of overweight - Feng, Xiaoqi; Wilson, Andrew (My University, 2022)
Some evidence indicates under-perception of overweight is associated with lower levels of weight loss. This might be due to 'visual normalisation' of overweight through comparisons made in communities where average body mass index (BMI) is high, resulting in under-perception of overweight, which in turn, may protect against negative weight-related self-perceptions and/or reduce motivation to lose weight. Evidence in support of this hypothesis was found initially in a precision-weighted multilevel logistic regression analysis of 3729 overweight Australians aged >18 y, after adjusting for age, sex and area-level disadvantage. Participants whose BMI was -1 kg/m2 or less than the community mean BMI had lower odds of weight-related dissatisfaction (OR = 0.64, 95%CI = 0.51-0.80) and perceived overweight (OR = 0.56, 95%CI = 0.45-0.70), compared with peers whose BMI was within ± 1 kg/m2 of the community mean. Moreover, participants whose BMI was 1 kg/m2 or greater than the community mean BMI had higher odds of weight-related dissatisfaction (OR = 1.97, 95%CI = 1.69-2.30) and perceived overweight (OR = 2.81, 95%CI = 2.41-3.28) when compared to the same reference group. These findings were consistent for men and women; however, they were attenuated towards the null and rendered statistically insignificant after adjustment for personal BMI. Overall, these results indicate that among adults who are overweight, personal BMI, rather than the relative difference between personal and community BMI, is the stronger determinant of weight-related perception and satisfaction.
Social Science & Medicine
Keywords: Health and wellbeing